Learning Strategies in Drum Band Extracurricular to Enhance Self-Confidence and Responsibility in Early Childhood - Ridwanulloh, M. Ubaidillah; Aini, Choirum Zatul; Derramas, Clarissa Ayangco (Indonesian Journal of Multidisciplinary Educational Research, 2024)
The aim of this research is to investigate the influence of drum band extracurricular learning on self-confidence and responsibility among early childhood learners. The research methodology adopts a qualitative approach, specifically a Case Study design. Descriptive data is obtained through interviews, observations, and documentation involving the school principal, two teacher assistants, two coaches, and parents of students from TK Bhayangkari 87 Mojosari. Data analysis involves data reduction, data presentation, and drawing conclusions. The findings reveal that the coaching model utilized direct instructional methods, where coaches demonstrated and provided examples to the children. The drill method, involving repetition, was also employed. Initially, the coach introduced the instruments to the children and allocated them into groups based on the drum band instruments. The evaluation process involved addressing issues raised during each meeting. Additionally, coaches optimized learning through the use of rewards and punishments. The impact of the drum band extracurricular at TK Bhayangkari 87 Mojosari includes fostering self-confidence, independence, socialization skills, and responsibility among the children. These results highlight the effectiveness of the learning strategies employed in the extracurricular program in enhancing holistic development among early childhood learners.